Perception of Nursery Students about Concept of Gender. - Aysel, Ozdemir; Nevin, Utkualp; Hicran, Yildiz; Neriman, Akansel; Aylin, Pallos (International Journal of Caring Sciences)
Background: Concept of gender effects the society and must be put into account by the health caregivers. Aim: This study was performed in order to examine the percetions of nursery students about concept of gender Methods: This descriptive study was carried with last year students who enrolled in faculty of Health Sciences Nursing Program during 2017-2018 academic year. Universe of this study was last year nursing studens and sample was consisted of 63 students who volunteered to participate in to this study. Results: The mean age of the students was 21.63 ± 0.86 and 39.7% were male. Mean age of the nursing students was calculated as 21.63±0.86 years and 60.3% of them were females. %). Most of the students report (96.8%) that being a woman is very hard and women are ussually responsible from various things in home. One of the most important responsibilities of women is to care for her children ( 95.2%). If the expectations from women decreases in the society the women's life will be easier according to nursing students (65.1%). Conclusion:Students have various perceptions related to women. The economic distress and social expectations arising from the political and financial problems in the society and the concern of securing the future of the family and children have great impact on the the decisions of families. Different studies need to be conducted to determine the the perception of students problems related to concept of gender and family patterns.